REVISING THE QUESTION OF TERMINOLOGY AND CLASSIFICATION OF BRUXISM - E. I. Boykova; P. N. Geletin; N. V. Ginali; N. N. Maslova; N. V. Yureva (Бюллетень сибирской медицины)
To date, there is no consolidated opinion regarding the terminology and classification of bruxism. The following terms are used for determination of unconscious strong compression teeth: “effect Karolyi”, “stridor dentium”, occlusal neurosis, odonterizm, “bruksomaniya”, “parafunctional activity of masticatory muscles”. Because of the disease nature the polyethiologic symptom group is develops that complicates the disease representation. The authors are recommend the usage “bruxism” term in everyday practice and as the most well-established and popular in the medical practice. The primary point of our study was identification of the pathognomonic parameters on electroencephalogram in patients with bruxism. As result of the study it was identified that the border type of EEG was registered statistically higher in pa-tients with parafunctional activity of masticatory muscles than in control group. The results are consistent with global trends, in respect that neuroscientists are systematize bruxism to “parasomnias”, (according to ICD 10) which are characterized by minor changes in the basic rhythm which were identical to findings that we revealed in the study group.